Performance enhancement techniques for indirect mode solar dryer: A review. (2023) - Kale, Sunil G.; Havaldar, Sanjay N.
Abstract: Drying of agricultural product is a process that requires a lot of energy. Higher cost, shortage of conventional fuels and threats to environment attracts usage of solar energy all over the world. Due to substantial increased concerns towards ecosystem and sustainability of resources, use of renewable energy resources has been observed in case of drying of products. Various kinds of solar dryers are present in the field of agriculture. Indirect Type Solar Drying (ITSD) is the most widely used dryer for drying of agricultural products. The present review paper mainly focuses on key strategies/techniques available to improve efficiency of indirect solar drying systems.